2022
DOI: 10.3390/nu14163285
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Diet-Related Diseases and Dietary Risk Factors: A 2022 Nationwide Cross-Sectional Survey among Adults in Poland

Abstract: A suboptimal diet is a risk factor for numerous non-communicable diseases. This study aimed to assess the level of knowledge on diet-related diseases and dietary risk factors among adults in Poland as well as to identify factors associated with awareness of diet-related diseases and dietary risk factors. This cross-sectional survey was carried out in July 2022 on a representative sample of adults in Poland. Data were received from 1070 individuals (53.3% females) aged 18–89 years. Out of eight diet-related dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The number of household members and educational level were the only factors significantly associated with a higher level of awareness of tobacco smoking as a diabetes risk factor. In this study, a high level of awareness of overweight/obesity and unhealthy diet as a risk factor for diabetes may result from extensive campaigns on di-et-related diseases that were carried out in Poland in recent years ( 43 ). We can hypothesize that a low level of awareness of alcohol and tobacco consumption as a risk factor for diabetes may result from a relatively low number of educational campaigns on diabetes risk factors or its limited effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The number of household members and educational level were the only factors significantly associated with a higher level of awareness of tobacco smoking as a diabetes risk factor. In this study, a high level of awareness of overweight/obesity and unhealthy diet as a risk factor for diabetes may result from extensive campaigns on di-et-related diseases that were carried out in Poland in recent years ( 43 ). We can hypothesize that a low level of awareness of alcohol and tobacco consumption as a risk factor for diabetes may result from a relatively low number of educational campaigns on diabetes risk factors or its limited effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only less than 3% of Australians and less than 2% of Slovenians consumed vegetables as a part of the snacking occasions. A very recent study showed that the majority of Polish adults are aware of the importance of vegetable and fruit intake, the negative effects of the consumption of sugar and salt, and the related dietary risk factors [ 40 ]. Nevertheless, many people still do not meet the recommended fruit and vegetable intakes (e.g., [ 41 , 42 , 43 ]), even though research is consistent that fruits and vegetables have beneficial effects on our overall physical and mental health [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the model can be further improved if these missing variables, such as alanine aminotransferase, serum calcium ions and oedema, are added in future studies. 33 Thirdly, we only used the data for the internal veri cation of our model, and other external data still need to be used to further verify its performance and clinical applicability.…”
Section: Discussionmentioning
confidence: 99%